ANALISIS LITERATUR TENTANG PENGARUH METODE RECIPROCAL TEACHING TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR - Shahana Nur Aini Sabila; Hermawan Wahyu Setiadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Reading comprehension is a crucial component of elementary school students' basic literacy, yet literacy achievement in Indonesia remains challenging. This article aims to analyze the effectiveness of the Reciprocal Teaching (RT) method in improving elementary school students' reading comprehension through a systematic literature review. The literature analyzed includes relevant primary and secondary sources from the 2020–2026 period. The study results indicate that RT tends to improve reading comprehension, student engagement, and metacognitive skills through four main strategies: predicting, questioning, clarifying, and summarizing. However, implementing RT requires teacher preparedness and gradual adjustments to reduce students' initial cognitive load. Overall, RT is a relevant and adaptive learning strategy to support strengthening reading literacy in elementary schools, including within the context of the Independent Curriculum. Keywords: Reciprocal Teaching, Reading Comprehension, Elementary School.